Direct to Angiography vs Repeated Imaging Approaches in Transferred Patients Undergoing Endovascular Thrombectomy - Sarraj, Amrou; Goyal, Nitin; Chen, Michael; Grotta, James C; Blackburn, Spiros; Requena, Manuel; Kamal, Haris; Abraham, Michael G; Elijovich, Lucas; Dannenbaum, Mark; Mir, Osman; Tekle, Wondwossen G; et al. (JAMA neurology, 2021)
A direct to angiography (DTA) treatment paradigm without repeated imaging for transferred patients with large vessel occlusion (LVO) may reduce time to endovascular thrombectomy (EVT). Whether DTA is safe and associated with better outcomes in the late (>6 hours) window is unknown. Also, DTA feasibility and effectiveness in reducing time to EVT during on-call vs regular-work hours and the association of interfacility transfer times with DTA outcomes have not been established. To evaluate the functional and safety outcomes of DTA vs repeated imaging in the different treatment windows and on-call hours vs regular hours. This pooled retrospective cohort study at 6 US and European comprehensive stroke centers enrolled adults (aged ≥18 years) with anterior circulation LVO (internal cerebral artery or middle cerebral artery subdivisions M1/M2) and transferred for EVT within 24 hours of the last-known-well time from January 1, 2014, to February 29, 2020. Repeated imaging (computed tomography with or without computed tomographic angiography or computed tomography perfusion) before EVT vs DTA. Functional independence (90-day modified Rankin Scale score, 0-2) was the primary outcome. Symptomatic intracerebral hemorrhage, mortality, and time metrics were also compared between the DTA and repeated imaging groups. A total of 1140 patients with LVO received EVT after transfer, including 327 (28.7%) in the DTA group and 813 (71.3%) in the repeated imaging group. The median age was 69 (interquartile range [IQR], 59-78) years; 529 were female (46.4%) and 609 (53.4%) were male. Patients undergoing DTA had greater use of intravenous alteplase (200 of 327 [61.2%] vs 412 of 808 [51.0%]; P = .002), but otherwise groups were similar. Median time from EVT center arrival to groin puncture was faster with DTA (34 [IQR, 20-62] vs 60 [IQR, 37-95] minutes; P < .001), overall and in both regular and on-call hours. Three-month functional independence was higher with DTA overall (164 of 312 [52.6%] vs 282 of 763 [37.0%]; adjusted odds ratio [aOR], 1.85 [95% CI, 1.33-2.57]; P < .001) and during regular (77 of 143 [53.8%] vs 118 of 292 [40.4%]; P = .008) and on-call (87 of 169 [51.5%] vs 164 of 471 [34.8%]; P < .001) hours. The results did not vary by time window (0-6 vs >6 to 24 hours; P = .88 for interaction). Three-month mortality was lower with DTA (53 of 312 [17.0%] vs 186 of 763 [24.4%]; P = .008). A 10-minute increase in EVT-center arrival to groin puncture in the repeated imaging group correlated with 5% reduction in the functional independence odds (aOR, 0.95 [95% CI, 0.91-0.99]; P = .01). The rates of modified Rankin Scale score of 0 to 2 decreased with interfacility transfer times of greater than 3 hours in the DTA group (96 of 161 [59.6%] vs 15 of 42 [35.7%]; P = .006), but not in the repeated imaging group (75 of 208 [36.1%] vs 71 of 192 [37.0%]; P = .85). The DTA approach may be associated with faster treatment and better functional outcomes during all hours and treatment windows, and repeated imaging may be reasonable with prolonged transfer times. Optimal EVT workflow in transfers may be associated with faster, safe reperfusion with improved outcomes.